ICT and exporting: the effects of broadband on the extensive margin of business service exports. - Kneller, Richard; Timmis, Jonathan (Wiley, 2016)
Over recent decades the global economy has witnessed rapid growth of international trade in services. This has been particularly true of service-intensive countries such as the UK. Developments in information and communication technologies are an obvious explanation for this. We provide empirical evidence for the effects of broadband use on the firm-extensive margin of UK service exports. To deal with the issue of causality we build a novel instrument that exploits exogenous variation in access to broadband technologies due to the historic telephone network. We find evidence for a causal effect from the internet on trade in business services, but no evidence for an effect on trade in services more generally.